2014
DOI: 10.5114/wiitm.2014.43021
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic complications after vascular interventions.

Abstract: IntroductionLymphorrhea due to classical and mini-invasive surgical interventions on femoral and popliteal arteries is a serious hindrance to patient treatment. Depending on the experience of a particular center, the incidence and frequency of this type of complication may constitute a serious clinical problem. While the level of lymphorrhea intensity and its duration result in certain foreseeable consequences, their treatment can be a time-consuming and multistep procedure.AimTo compare different types of vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
(25 reference statements)
0
12
0
Order By: Relevance
“…In addition, redo surgery has been identified as a significant risk factor for surgical site and vascular graft infection, 13 bleeding from infected regions and septicemia. 14 To reduce the risk of such complications, a percutaneous approach was employed in all patients of this series.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, redo surgery has been identified as a significant risk factor for surgical site and vascular graft infection, 13 bleeding from infected regions and septicemia. 14 To reduce the risk of such complications, a percutaneous approach was employed in all patients of this series.…”
Section: Discussionmentioning
confidence: 99%
“…23 In general, surgical procedures requiring groin incisions are associated with a higher rate of wound complications. 24 The presented study was able to identify factors, which may be associated with an increased risk for deteriorated wound healing. Former intravenous drug abuse and previous venous interventions as well as surgical procedures like thrombectomy showed an increased, but not significant association with wound complications.…”
Section: Discussionmentioning
confidence: 97%
“…23 In general, surgical procedures requiring groin incisions are associated with a higher rate of wound complications. 24…”
Section: Discussionmentioning
confidence: 99%
“…Lymphatic leak is a serious complication of vascular surgery that incurs significant cost to the healthcare system and morbidity to the patient [1][2][3][4][5]. Disruption of lymphatic channels during vascular surgery and failure of subsequent healing may result in persistent leakage, presenting as lymphocele or lymphocutaneous fistula, and may occur in as many as 18% of arterial interventions [6]. A variety of factors have also been identified that may predispose patients to lymphatic leak including surgical procedure and graft type, incision techniques, as well as patient demographics [3,5,7].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of factors have also been identified that may predispose patients to lymphatic leak including surgical procedure and graft type, incision techniques, as well as patient demographics [ 3 , 5 , 7 ]. As a result, patients who develop postvascular dissection lymphatic leak have delayed wound healing, are at greater risk of infection and graft rejection, and spend more time in the hospital, thereby increasing the cost of care [ 2 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%